Bioethical Principles of Use of Experimental Animals in Biomedical Research - Rachmat Hidayat; Patricia Wulandari (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Research is an activity carried out based on scientific principles and methods systematically to obtain information, data, and information from related subjects, with understanding the theory and proving assumptions and / or hypotheses. The resultsobtained are conclusions that can be applied or become additional knowledge for the advancement of science. However, research activities must still respect the rights and dignity of research subjects. Health research includes biomedical, epidemiological, social, and behavioral research. Some health research can be done in vitro, using mathematical models, or computer simulations.